In vitro H1-receptor antagonist activity of methanolic extract of tuber of Stephania glabra - Nisar Ahmad Khan; Dinesh Kumar; Zulfiqar Ali Bhat; Vijender Kumar; Navneet Nagpal; Santosh S. Bhujbal (Bangladesh Pharmacological Society, 2011)
In the present study, methanolic extract of tuber of Stephania glabra was evaluated for H1-bloker activity by employing in vitro screening models of guinea pig ileum and goat tracheal chain preparation. Goat isolated trachea and guinea pig ileum contracted to histamine in a dose-dependent manner while chlorpheniramine blocked this effect. The methanolic extract produced significant dose-dependent H1-receptor antagonist activity by blocking histamine-induced contraction.